A pleiotropic effect of the APOE gene: association of APOE polymorphisms with multibacillary leprosy in Han Chinese from Southwest China. (18th April 2018) - Wang, D.; Zhang, D.‐F.; Li, G.‐D.; Bi, R.; Fan, Y.; Wu, Y.; Yu, X.‐F.; Long, H.; Li, Y.‐Y.; Yao, Y.‐G.
Summary: This is a study by investigators from the Chinese Academy of Sciences and Dermatology departments based in Yunnan province in China. Basing their research on a previous observation that patients with leprosy have a lower frequency of dementia due to Alzheimer's Disease than patients without, they investigated whether there was any link between the occurrence of leprosy and the human genes involved in the formation and breakdown of different lipids or fats, processes that are key steps in the development of both Alzheimer's disease as well as the invasion of skin and nerves in leprosy. They searched for a link between a gene called Apolipoprotein E (APOE) which is known to be involved in Alzheimer's and found that certain mutations in the gene were more common in patients with leprosy. They suggested that this might lead to an increase in a lipid binding protein found in blood plasma and that this in turn would aid the survival of the bacteria that cause leprosy, Mycobacterium leprae, thus allowing it to spread and the disease to develop. Abstract : Linked Article: Wang et al. Br J Dermatol 2018; 178 :931–939